TEORI HUKUM SEJARAH (HISTORICAL LEGAL THEORY) DI INDONESIA: KAJIAN SISTEMATIS MELALUI METODE SYSTEMATIC LITERATURE REVIEW - Nasrullah Nasrullah; Jalaluddin, Ilham Akbar (JOURNAL OF LAW AND NATION, 2025)
Historical Legal Theory emphasises that law is a product of the development of culture, tradition and history of society. In the Indonesian context, the national legal system was formed from the interaction between customary law, Islamic law, and colonial law inherited by colonialism. This research aims to examine the role and relevance of Legal History Theory in the formation of the legal system in Indonesia through a Systematic Literature Review (SLR) approach. This method is used to identify, analyse, and synthesise relevant literature related to the development of Indonesian law in a historical perspective. The results showed that the development of law in Indonesia was influenced by a complex historical process, where adaptation and acculturation between customary, Islamic, and colonial laws formed the national legal framework. In addition, it was found that the Legal Theory of History plays an important role in explaining the dynamics of legal change along with social, political, and cultural developments. The research also identifies significant historical implications for contemporary legal reform, particularly in the harmonisation of local and modern legal traditions. This study makes an academic contribution by providing a comprehensive theoretical framework for understanding the relationship between history and law in Indonesia. Practically, it offers insights for policymakers in designing a just and contextualised legal system. As such, this study not only strengthens academic understanding of Indonesian law, but also provides strategic guidance for relevant and sustainable legal development.